Pelatihan Pembuatan Media Promosi dan Pengajuan Kredit Perbankan di Kelurahan Pangkalan Jati, Cinere, Depok - Diana Triwardhani; Lina Aryani (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON MAKING PROMOTION MEDIA AND APPLICATION FOR BANKING LOANS IN PANGKALAN JATI VILLAGE, CINERE, DEPOK. Promotion is an important thing that must be done in every business. Promotion can be done through social media and others, like on Instagram, Facebook. In addition, people who have small-scale businesses with no large capital have a desire to add business but no funds. Therefore, the only way is to borrow funds from the bank, because the bank is the savings and loan institution that has clear rules for providing credit. However, many of these start-up businesses do not yet understand how to make loans, this is the problem that will be discussed at the abdimas which will be held in the village of Pankalan Jati, Cinere Depok, in addition to the media promotion that will be carried out by them.